A Social Issue in the Information Society: Stress and Strategies for Coping with Stress - RECEPOĞLU, Serpil; RECEPOĞLU, Ergün (Kastamonu Egitim Dergisi, 2021)
Stress, which has become a social problem in recent years, can occur in all areas of life. In today's information societies, globalization and economic liberalization, trying to adapt to complex life conditions in an intensive information, communication and technology network cause him to feel pressured and wear out. In this context, stress is also expressed as "the disease of information society". This intensity affects the whole life of a person and reduces their self-esteem and efficiency. It is especially important to evaluate all aspects of stress from the individual's position, the state of environmental factors, from a sociological perspective. Natural disasters, epidemics, economic crises and wars have continued their effects on people for many years by affecting the masses and causing great losses. The ability of individuals to live happily and peacefully by protecting their health depends on their ability to manage stress well and to use effective coping strategies appropriate for them. In this study, strategies for coping with stress, which has become a social question in the information society, were examined all aspects of stress from the individual's position, the state of environmental factors, from a sociological perspective.